Excess weight in high-risk pregnant women and factors associated with excessive weight gain (Research, Society and Development, 2022)
Objective: To evaluate the factors associated with excessive weight gain in high-risk pregnant women with excess weight. Methodology: Descriptive, quantitative study, carried out from August to December 2019, being evaluated pregnant women with excess weight, admitted to the obstetric center / rooming-in of a university hospital in Recife-PE. The previous and current nutritional status was determined through the Body Mass Index, being classified according to the adult population and the gestational age, respectively. Maternal weight gain was also investigated, using the ranges recommended by the Institute of Medicine. Fisher's exact and Pearson's chi-square tests were used in the statistical analysis. The significance level for the tests was 5%. Results: 107 high-risk pregnant women with a mean age of 28.22±6.12 years were included in the study. This research found that factors such as income, nulliparity, gestational hypertension and pre-gestational BMI are associated with the development of excessive weight gain and gestational obesity. Conclusion: Excessive weight gain was associated with lower family income, last gestational trimesters and gestational hypertension. We emphasize the importance of monitoring weight gain, with special attention to low-income women with pre-gestational excess weight.